2012
DOI: 10.1097/aln.0b013e31824a88d0
|View full text |Cite
|
Sign up to set email alerts
|

Using Process Analysis to Assess the Impact of Medical Education on the Delivery of Pain Services

Abstract: Background:The medical, social, and economic effects of the teaching mission on delivery of care at an academic medical center (AMC) are not fully understood. When a freestanding private practice ambulatory clinic with no teaching mission was merged into an AMC, a natural experiment was created. The authors compared process measures across the two settings to observe the differences in system performance introduced by the added steps and resources of the AMC's teaching mission. Methods: After creating process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Appt.=appointment. Adapted with permission from Lippincott Williams and Wilken/Wolters Kluwer Health 14. Promotional and commercial use of the material in print, digital or mobile device format is prohibited without the permission from the publisher Lippincott Williams & Wilkins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Appt.=appointment. Adapted with permission from Lippincott Williams and Wilken/Wolters Kluwer Health 14. Promotional and commercial use of the material in print, digital or mobile device format is prohibited without the permission from the publisher Lippincott Williams & Wilkins.…”
Section: Methodsmentioning
confidence: 99%
“…Type 1=patients who come to the clinic for an initial visit; type 2=patients who come for a follow-up visit; type 3=patients who come for services routinely handled by the physician's assistant (P/A). Reproduced with permission 14. Promotional and commercial use of the material in print, digital or mobile device format is prohibited without the permission from the publisher Lippincott Williams & Wilkins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have been limited in size and have had conflicting findings. For example, 2 studies 11,12 found that the presence of trainees was associated with improved clinical efficiency by shortening patient wait times, whereas another study 13 found that trainees were associated with lengthened patient wait times and overall appointment times. This issue has implications for clinical efficiency and physician reimbursement models, particularly in academic medical centers.…”
mentioning
confidence: 99%
“…Third, this case can be used along with the DES models provided which have been calibrated in the actual clinics and used in detailed research on clinic performance (Williams et al 2012(Williams et al , 2014(Williams et al , 2015Chambers et al 2016) Instructors can use the data and DES models in a variety of ways, depending on the emphasis of the course and background of the student population. This is useful because DES models are becoming increasingly common as elements of quality improvement (QI) efforts in healthcare settings (Jacobson et al 2006).…”
Section: Existing Case Studiesmentioning
confidence: 99%